Pemeriksaan Hemoglobin Pada Petugas SPBU Di Daerah Glugur Rimbun Kabupaten Deli Serdang Tahun 2021 - Radina YM Ginting; Yuspita Wahyu (Journal of Pharmaceutical and Sciences, 2023)
Gas station workers are one of the workers who have a high risk of exposure to toxic substances that are exposed to fuel because every day they work in a place related to motorized vehicles, exposure to gases which, if inhaled, enter the human body in high levels, can inhibit the formation process. hemoglobin. Hemoglobin is a protein molecule in red blood cells that functions as a medium for transporting oxygen from the lungs throughout the body and carrying carbon dioxide from the body's tissues to the lungs. When hemoglobin is reduced, the body will become tired, lethargic, drowsy, and lose concentration more quickly. Hemoglobin that is too low can cause a disease known as Anemia. The purpose of this study was to determine hemoglobin levels in gas station attendants. This research was conducted using the blood cyanmethemoglobin method using Drabkins reagent. The population of this study were gas station attendants in the Glugur Rimbun area, Deli Serdang Regency with a sample of 14. This research was conducted at the North Sumatra Regional Health Laboratory. The results of this study showed that 21% had below normal Hb values.